Restorative justice within the criminal justice system - Vasiljević-Prodanović Danica (Temida)
Positioning of restorative justice within the criminal justice system is one of the current questions preoccupying theorists and practitioners in the field. During decades restorative justice processes have been predominantly used within juvenile justice systems for dealing with minor offences committed by juveniles. Number of jurisdictions in Europe, USA, Canada, Australia have criminal codifications containing provisions that enable use of restorative justice processes in aim of diversion. Recent initiatives create possibility of applying restorative procedure in cases of serious crimes committed by adult offenders. This article reviews theoretical discussions and practical issues relating the scope and tasks of restorative justice within criminal justice, which may contribute to the development and use of restorative processes in our criminal justice system.